Pengaruh Audit Internal, Sistem Informasi Akuntansi Dan Komitmen Organisasional Terhadap Kualitas Laporan Keuangan - Agrayi Afifa Putri; Cris Kuntadi; Yetri Martika Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The influence of internal audit, accounting information systems and organizational commitment on the quality of financial reports is research that aims to determine the influence of these three factors on the quality of financial reports. This research uses a descriptive method. The units of analysis in this research are accounting information systems, organizational commitment, and internal audit. The research results show that Internal Audit, Accounting Information Systems, and Organizational Commitment have a positive and significant effect on the quality of financial reports. Internal audit also has an important role in supervising and controlling organizational activities, which will affect the quality of financial reports. The accounting information system aims to collect, process and convey relevant data and information to interested parties, both internal and external parties. Organizational commitment can also influence employee interest, propensity to stay, and propensity to leave, which will influence audit performance.